Changes in levels of Interleukin-6 (IL-6) and Interleukin-8 (IL-8) in the Serum of Preterm Delivery Pregnant Women Affected by Gingivitis - Maddah, Shaden H.; Taha, Ghada I. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Periodontal disease increases local and systemic inflammatory responses in pregnant women, which may lead to premature delivery.Objectives: To detect maternal serum levels of proinflammatory cytokines (interleukine-6, interleukin-8) with preterm delivery in pregnant women suffering from gingivitis.Methods: In this case-control study, a total of 85 pregnant women were included in the study, of whom 55 had gingivitis: 25 preterm deliveries and 30 full-term deliveries. Thirty healthy pregnant women with healthy gingiva were in the control group. They were selected from Al-Ramadi Teaching Hospital for Gynaecology and Paediatrics, from November 2022 to May 2023. Blood samples were collected from all participants, and the biomarkers and cytokines were detected by immunosorbent assay kits.Results: The current study showed an increased level of interleukin-6 and interleukin-8 in the pre-term delivery gingivitis group followed by full-term delivery pregnant groups having gingivitis compared with the control group, with statistically highly significant differences.Conclusion: Pregnant women with gingivitis with the highest levels of Interlukine-6 and Interlukine-8 were more prone to have premature delivery than those with lower levels of Interleukins and those without gingivitis.